PTC-209 Anti-Cancer Effects Involved the Inhibition of STAT3 Phosphorylation - Sulaiman, Shahrazad; Arafat, Kholoud; Iratni, Rabah; Attoub, Samir (Frontiers in Pharmacology, 2019)
Lung, breast, and colorectal cancers are leading cancer-related deaths despite many therapeutic options including targeted- and immuno-therapies. Here, we investigated the impact of PTC-209, a small-molecule Bmi-1 inhibitor, on human cancer cell viability alone and in combination with anticancer drugs namely cisplatin, oxaliplatin, 5-fluorouracil, camptothecin, and Frondoside-A, and its impact on cellular migration and colony growth in vitro and on tumor growth in ovo. We demonstrate that PTC-209, cause a concentration- and time-dependent decrease in the cellular viability of the lung cancer cells (LNM35 and A549), breast cancer cells (MDA-MB-231 and T47D), and colon cancer cells (HT-29, HCT8/S11, and HCT-116). Similarly, treatment with PTC-209 significantly decreased the growth of LNM35, A549, MDA-MB-231, and HT-29 clones and colonies in vitro and LNM35 and A549 tumor growth in the In ovo tumor xenograft model. PTC-209 at the non-toxic concentrations significantly reduced the migration of lung (LNM35 and A549) and breast (MDA-MB-231) cancer cells. Moreover, we show that PTC-209 at the concentration of 1 μM enhances the anti-cancer effects of Frondoside-A in lung, breast, and colon cancer cells as well as the effect camptothecin in breast cancer cells and the effect of cisplatin in lung cancer cells in vitro. However, PTC-209 failed to enhance the anti-cancer effects of oxaliplatin and 5-fluorouracil in colon cancer cells. Treatment of lung, breast, and colon cancer cells with PTC-209 (1 and 2.5 μM) for 48 h showed no caspase-3 activation, but a decrease in the cell number below the seeding level suggesting that PTC-209 reduces cellular viability probably through inhibition of cell proliferation and induction of cell death via a caspase-3 independent mechanism. Molecular mechanism analysis revealed that PTC-209 significantly inhibited the STAT3 signaling pathway as early as 30 min post-treatment. Our findings identify PTC-209 as a promising anticancer agent for the treatment of solid tumors either alone, and/or in combination with the standard cytotoxic drugs cisplatin and camptothecin and the natural product Frondoside-A.